Rekomendasi Penerima Bantuan Siswa Miskin Berbasis Web Menggunakan Metode Simple Additive Weighting (SAW) di SDN Panunggangan 4 - Muhamad Dhafa Hasballah; Shevti Arbekti Arman; Elliya Sestri (Jurnal Teknologi Informasi (JUTECH), 2024)
The development of a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to evaluate and select students eligible for assistance based on predetermined criteria has been successfully accomplished. The SAW method involves six assessment criteria: family members (0.1), parental employment status (0.15), residence status (0.1), monthly income (0.3), student absenteeism (0.15), and academic achievement (0.2). The primary aim of this DSS is to streamline the decision-making process for teachers and administrators at SDN Panunggangan 4. Employing this algorithm, the system automatically ranks students based on their highest scores to prioritize those deserving of assistance. The study was centered on 32 sixth-grade students. Moving forward, it is hoped that this application can be enhanced and implemented more extensively.